Micro and Macro Determinants of Non-performing Loans - Messai, Ahlem Selma; Jouini, Fathi (International Journal of Economics and Financial Issues, 2013)
In this study we tried to detect the determinants of non-performing loans for a sample of 85 banks in three countries (Italy, Greece and Spain) for the period of 2004-2008. These countries have faced financial problems after the subprime crisis on 2008. The variables used are macroeconomic variables and specific variables to the bank. The macroeconomic variables are included the rate of growth of GDP, unemployment rate and real interest rate with respect to specific variables opted for the return on assets, the change in loans and the loan loss reserves to total loans ratio (LLR/TL). After the application of the method of panel data, we found the problem loans vary negatively with the growth rate of GDP, the profitability of banks’ assets and positively with the unemployment rate, the loan loss reserves to total loans and the real interest rate. Keywords: Non-performing loans; Macroeconomic determinants; Bank specific determinants JEL Classifications: E32; E44; F30; G2